The Effectiveness of City Square Development as an Instrument for Green Open Space Policy in Depok City - Arifiani, Friska; Ridwan Maksum, Irfan (Riviera Publishing, 2023)
Green open space is one of the important elements that must exist in every urban area. The City Government of Depok, as one of the areas that is considered to need improvement in the provision of green open spaces, has made a policy strategy by building town squares and parks in every village. This study aims to analyze the effectiveness of the development of the town square as an instrument of green open space policy in Depok City. The research uses a post-positivist method where data is collected through interviews and observations, which are then processed into descriptive narratives. The results of the study show that there are still two indicators that need to be improved, where the level of interest of the target group and the use of space are obstacles in the implementation of green open space policies in city squares. Some of the factors that make these indicators ineffective include lack of community participation, lack of resources, and discrepancies between the initial concept and the results. Then it influences the indicators of clarity of agreement on policy objectives and control of spatial use. Therefore, the development of the Alun-Alun as an instrument of green open space policy is still not effective so it is necessary to add space or Alun-Alun to meet the needs of green open spaces in Depok City.